Dielectric Relaxation Behavior of Halobenzene Confined in the δ‐Phase of Syndiotactic Polystyrene. Issue 1 (13th April 2023) - Urakawa, Osamu; Kobayashi, Hideo; Inoue, Ryosai; Kaneko, Fumitoshi; Inoue, Tadashi
Abstract: Syndiotactic polystyrene (sPS) incorporates low‐mass guest molecules to form a co‐crystalline structure, the δ‐phase, in which the guest molecules are confined within a nanosized space. Under such spatial constraints, what factors determine the dynamics of the guest molecules? This is an interesting question and needs to be clarified toward the functionalization of sPS/functional guest systems. In this study, the size effect of the guest molecules and use monosubstituted halobenzenes (fluorobenzene, chlorobenzene, bromobenzene, and iodobenzene) to systematically change the molecular size is focussed. Since halobenzene has a large electric dipole moment, dielectric relaxation measurements can effectively detect its molecular motion. This study aims to identify the guest dynamics in the δ‐phase by dielectric relaxation measurement and examines the molecular length dependence of the rotational relaxation times and their activation energies.